Environmental, Social and Governance Reporting under IFRS S1–S2: Significance and Implementation in Thai and International Contexts - Clements, Mathas (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
Over the past decade, Environmental, Social, and Governance (ESG) awareness has become a key driver in global business operations. Organizations are now expected to disclose transparent and reliable information to stakeholders, beyond traditional financial reporting. In response, the International Sustainability Standards Board (ISSB) developed IFRS S1 and IFRS S2 to create a globally consistent and comparable framework for sustainability reporting. This article has three objectives: (1) to analyze the importance of ESG that led to the development of these standards, (2) to explain the core principles of IFRS S1 and S2, and (3) to examine the application, challenges, and opportunities for Thai businesses. This study is documentary research, compiling and synthesizing information from ISSB standards and related regulatory documents. The findings indicate that adopting these standards will enhance transparency and credibility in capital markets. However, the Thai business sector faces significant challenges, such as the complexity of data collection and a shortage of skilled personnel. Conversely, it presents opportunities for accessing green finance and gaining a competitive advantage. The article concludes that applying these standards is not merely a matter of compliance but a critical strategic investment for the sustainable growth of Thai businesses.